Does the “Words of Affirmation” English Podcast Have Any Positive Influence on Students' Listening Skills? - Zulfikar Noor; Sholihatul Hamidah Daulay (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2023)
A plethora of studies in Indonesia have investigated the research of the use of technology on students’ listening skills but research about the use of English word affirmation podcasts in improving students' listening skills based on student perception is still limited. This study aimed to investigate students' views on the effect of listening to “English words of affirmation” on their listening skills. This research employed a qualitative case study methodology. By using a closed-ended questionnaire and a semi-structured interview, 24 English students from one of North Sumatera's state universities were recruited to fulfill the demographic survey. The participants were selected by using purposive sampling, as the researchers selected only those who frequently listened to “English word affirmation” in their daily lives to enhance their English proficiency, particularly their listening skills. The questionnaire was disseminated through a Google Form to collect the demographic survey of students who were familiar with listening to the “English word affirmation podcast”. The interview was then conducted via the Zoom application to delve deeper into students' perceptions of the positive influence of listening to the “English word affirmation podcast” on improving their listening skills. This study discovered that listening to the “English word of affirmation” podcast could improve students' listening skills. This study suggested that educators and students could use English word affirmation podcasts as a reference in the English learning process, particularly for listening skills.